2002
DOI: 10.1200/jco.2002.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oral Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor ZD1839 Is Generally Well-Tolerated and Has Activity in Non–Small-Cell Lung Cancer and Other Solid Tumors: Results of a Phase I Trial

Abstract: Rash and diarrhea, generally mild and tolerable at doses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
280
1
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 531 publications
(292 citation statements)
references
References 31 publications
6
280
1
5
Order By: Relevance
“…Gefitinib, an EGFR inhibitor, is a new molecule-targeting treatment for lung cancer. It is reported to have a considerable effect on females and nonsmokers, especially those with adenocarcinoma [6,11,12,21]. Analyses of single and multiple variables indicated better prognoses for patients with adenocarcinoma and patients treated with gefitinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gefitinib, an EGFR inhibitor, is a new molecule-targeting treatment for lung cancer. It is reported to have a considerable effect on females and nonsmokers, especially those with adenocarcinoma [6,11,12,21]. Analyses of single and multiple variables indicated better prognoses for patients with adenocarcinoma and patients treated with gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports suggest an epithelial growth factor receptor (EGFR) inhibitor has been effective in treating lung cancer [6,11,12,21]. The EGFR inhibitor is a new molecule-targeted agent for lung cancer that is reported to have a considerable effect on females and nonsmokers, especially those with adenocarcinoma [6,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, human breast cancer cells overexpressing HER2 or acquiring resistance to the oestrogen receptor (ER) antagonist, fulvestrant (Faslodex,ICI 182,780), have been reported to be particularly sensitive to gefitinib (McClelland et al, 2001;Moulder et al, 2001). Furthermore, phase I trials of gefitinib in patients with solid tumours refractory to standard chemotherapies have shown good tolerability and promising antitumour activity Herbst et al, 2002;Ranson et al, 2002). These findings suggest that gefitinib will be clinically useful in the treatment of patients with hormone-refractory breast cancer.…”
mentioning
confidence: 91%
“…In those clinical trials, various toxicities (mainly, acneiform rash and diarrhoea) were reported although the frequency and severity of these adverse events were relatively low (Dittrich et al, 2002;Herbst et al, 2002;Mendelsohn and Baselga, 2003). We have used self-antigen-derived peptides, such as SART1, SART3, and lck, in phase I clinical studies of individualised peptide vaccination for far advanced cancer patients.…”
Section: E/t Ratio (Times)mentioning
confidence: 99%